Preventing the next fragility fracture: a cross-sectional survey of secondary fragility fracture prevention services worldwide - Singh S. (2023)
BACKGROUND: There has been an increasing awareness of the public health impact of fragility fractures due to osteoporosis and the imperative of addressing this health burden with well-designed secondary fragility fracture prevention services (SFFPS). The objectives of this survey, conducted within the international membership of the Fragility Fracture Network (FFN), were to identify gaps in services and identify the needs for further training and mentorship to improve the quality of SFFPS provided to patients who sustain fragility fractures. METHODS: We conducted an electronic cross-sectional survey of FFN Secondary Fracture Prevention Special Interest Group (SIG) members from April 2021 to June 2021 using SurveyMonkey. The survey questions were developed by four SIG members from New Zealand, Australia, Canada and the Netherlands, who have experience in developing, implementing and evaluating SFFPS. The sampling framework was convenience sampling of all 1162 registered FFN Secondary Fracture Prevention SIG members. Descriptive analyses were performed for all variables and presented as frequencies and percentages. RESULTS: 69 individuals participated in the survey, from 34 different countries over six continents, with a response rate of 6% (69/1162). Almost one-third of respondents (22/69) were from 15 countries within the European continent. Key findings included: (1) 25% of SFFPS only included patients with hip fracture; (2) less than 5% of SFFPS had any mandatory core competencies for training; (3) 38.7% of SFFPS were required to collect key performance indicators; and (4) 9% were collecting patient-reported outcome measures. CONCLUSIONS: This survey identified key areas for improving SFFPS, including: expanding the reach of SFFPS to more patients with fragility fracture, developing international core competencies for health provider training, using key performance indicators to improve SFFPS and including the patient voice in SFFPS development. These findings will be used by the FFN to support SFFPS development internationally.